2021
DOI: 10.1186/s12942-021-00285-x
|View full text |Cite
|
Sign up to set email alerts
|

Coverage versus response time objectives in ambulance location

Abstract: Background This paper deals with the location of emergency medical stations where ambulances waiting to be dispatched are parked. The literature reports a lot of mathematical programming models used to optimize station locations. Most studies evaluate the models only analytically applying the same simplifying assumptions that were used in the modelling phase. In addition, they concentrate on systems operating one type of emergency units in homogeneous urban areas. The goal of our study is to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Since this model also minimizes the average response time, our results are compatible with the cited works. The average response time seems to be the most important indicator of EMS access, especially from the most critical patients' point of view, because it strongly affects the probability of survival for those patients [17,29,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this model also minimizes the average response time, our results are compatible with the cited works. The average response time seems to be the most important indicator of EMS access, especially from the most critical patients' point of view, because it strongly affects the probability of survival for those patients [17,29,33].…”
Section: Discussionmentioning
confidence: 99%
“…The MCLP model considers the expected number of patients. The expected numbers b j1 and b j2 of high-priority and low-priority patients, respectively, can be calculated using the age structure of the population in the city, and the emergency rates for the particular age categories [29].…”
Section: Setting Parameters In the Location Modelsmentioning
confidence: 99%
“…In addition, the background of many articles has validated response time as a significant factor for gaining better insight into the operational performance of EMS. Some works have demonstrated that the patient's mortality and recovery rates are highly influenced by the response time [11]- [14]. Using the same objective in this paper, the authors have considered response time as the prime attribute for estimating and improving the medical service provided by EMS.…”
Section: Litertaure Reviewmentioning
confidence: 98%
“…The fair objective function value f2(y) formulated by ( 3) expresses the number of users, whose time distance from the nearest located service facility exceeds given limit D. This objective follows the request of certain level of fairness in access to the provided service [5,18,22,23].…”
Section: Objectivesmentioning
confidence: 99%
“…From the scientific point of view, the public service system design problem belongs to the family of discrete network location problems, which have been studied and effectively solved by many authors [3,7,8,9,11,23,27,28]. As far as a concrete form of the problem is concerned, one of the most commonly used modelling concepts follows the weighted p-median problem [3,4,14,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%